Nonlinear effects in optical fibers - Ferreira, Mario F. S.; Sweet, William N.; Biemer, Steven M.; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley, 2010)
"The only book on the market to seamlessly explore the physical and technical aspects of nonlinear effects as well as their impacts and applications, Nonlinear Effects in Optical Fibers provides a comprehensible introduction to the complex nonlinear phenomena occurring within optical fibers. This valuable resource for students, researchers, and developers explores virtually all the latest and most significant research results in the field of nonlinear fiber optics, including: highly nonlinear and photonic fibers; intrachannel nonlinear effects; dissipative and dispersion-managed solitons; and potential applications of nonlinear effects in the area of optical signal processing"--
Frontmatter -- Introduction -- Electromagnetic Wave Propagation -- Optical Fibers -- The Nonlinear Schrødinger Equation -- Nonlinear Phase Modulation -- Four-Wave Mixing -- Intrachannel Nonlinear Effects -- Soliton Lightwave Systems -- Other Applications of Optical Solitons -- Polarization Effects -- Stimulated Raman Scattering -- Stimulated Brillouin Scattering -- Highly Nonlinear and Microstructured Fibers -- Optical Signal Processing -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Fiber optics; Nonlinear optics; TECHNOLOGY & ENGINEERING -- Fiber Optics; Fiber optics; Nonlinear optics; Electronic books